Studi Literatur Strategi Pemasaran Produk Pembiayaan KPR Syariah - Putri Rahma; Siregar, Pani Akhiruddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In facing competition, Islamic banking must have effective techniques to enter the market. Home Ownership Credit (KPR) is a financing product or loan given to home buyers with a financing scheme with a certain percentage. This research is a literature study on marketing strategies for KPR products at Sharia Banks, so that you can find out what discussions have been researched and what discussions need to be researched. This research uses qualitative research. There are 20 selected articles published from 2019-2022 which are grouped into two main topics, namely topics about implementative marketing strategies and marketing strategy models. The topic of implementative marketing strategies is the fewest articles with a percentage of 30%. And the topic of marketing strategy models is the most numerous article with a percentage of 70%. With the topic of Implementative marketing strategies, it can be concluded that several marketing strategies are widely implemented in Sharia Banks, namely: By providing affordable installments, collaborating with developers, advertising in various media, selling products with direct selling, and open tables at events. Meanwhile, with the topic of marketing strategy models, there are several models that can be used in Sharia Banks, namely 1. using the 4p or 7p marketing mix model, 2. Using SWOT analysis, and 3. Door to door strategy model. Discussions that need to be researched include marketing strategies in the digital era and the opportunities and obstacles experienced by Sharia Banks and Conventional Banks in implementing marketing strategies